2016
DOI: 10.1016/j.immuni.2016.08.017
|View full text |Cite
|
Sign up to set email alerts
|

mTORC1 and mTORC2 Kinase Signaling and Glucose Metabolism Drive Follicular Helper T Cell Differentiation

Abstract: SUMMARY Follicular helper T (Tfh) cells are crucial for germinal center (GC)formation andhumoraladaptiveimmunity. Mechanisms underlying Tfh cell differentiation in peripheral and mucosal lymphoid organs are incompletely understood. We report here that mTOR kinase complexes 1 and 2 (mTORC1 and mTORC2) are essential for Tfh cell differentiation and GC reaction under steady state and after antigen immunization and viral infection. Loss of mTORC1 and mTORC2 in T cells exerted distinct effects on Tfh cell signature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
322
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 289 publications
(349 citation statements)
references
References 45 publications
14
322
1
Order By: Relevance
“…Although previous studies 11 have suggested that Tfh, like Treg, utilize less glycolysis, mitochondrial respiration and as a consequence, mTOR function than Th1 cells, AZD2014 and RAPA both suppressed Tfh effectively. This is consistent with recent data 48 demonstrating that glucose metabolism and both mTORC1 and mTORC2 signaling are essential for Tfh differentiation and GC reaction in Peyer’s patches. In the latter study, mTORC2 was uniquely required for normal Tfh cell localization in PP, expression of Forkhead box protein 01 (Fox01) targets and nuclear exclusion of Fox01 upon inducible T cell costimulator ligation.…”
Section: Discussionsupporting
confidence: 94%
“…Although previous studies 11 have suggested that Tfh, like Treg, utilize less glycolysis, mitochondrial respiration and as a consequence, mTOR function than Th1 cells, AZD2014 and RAPA both suppressed Tfh effectively. This is consistent with recent data 48 demonstrating that glucose metabolism and both mTORC1 and mTORC2 signaling are essential for Tfh differentiation and GC reaction in Peyer’s patches. In the latter study, mTORC2 was uniquely required for normal Tfh cell localization in PP, expression of Forkhead box protein 01 (Fox01) targets and nuclear exclusion of Fox01 upon inducible T cell costimulator ligation.…”
Section: Discussionsupporting
confidence: 94%
“…In contrast, recent studies using conditional knockout mice showed that mTORC1 signaling was essential for induction of Tfh responses (30,31). These contradictory results may be explained by the different approaches used to silence mTOR activity.…”
Section: Discussionmentioning
confidence: 92%
“…In contrast, in Th1 cells mTORC2 has been reported to signal through Akt (Lee et al, 2010). In contrast to the situation for Th1 and Th17 cells, which exert their functions primarily within non-lymphoid tissues and which rely on one or other of the mTOR complexes for their differentiation, Tfh cells, which are restricted to germinal centers in secondary lymphoid organs, are dependent on both mTORC1 and mTORC2, since Tnfrsf4-cre -mediated deletion of Raptor or Rictor is sufficient to prevent their development (Zeng et al, 2016). …”
Section: Mtor In the Adaptive Immune Systemmentioning
confidence: 99%